Analisis Adopsi eSIM pada Generasi Z Menggunakan Model Modifikasi UTAUT2 - Naufal Aqiilah Pratama; Muhammad Rifqi Arviansyah (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2026)
eSIM is an innovation born from the rapid development of technology and digital connectivity. However, its adoption rate still faces a significant gap, with only 1 million eSIM users out of 332 million mobile subscribers in Indonesia. Generation Z, as digital natives and the largest demographic group at 75.49 million, accounts for 25.54% of internet users with an 87.80% penetration rate, making them a highly relevant subject to explore in understanding the phenomenon of this technology adoption intention. This study seeks to address the aspects influencing the intention to adopt eSIM among Generation Z in Indonesia by applying a modification to the UTAUT2 model. This quantitative research involved 203 Generation Z respondents collected through a purposive sampling method. Model testing was conducted by utilizing SEM-PLS analysis via the RStudio application and the SeminR module. The results show that Performance Expectancy, Social Influence, and Environmental Awareness have a positive and significant effect on eSIM adoption intention. Conversely, Effort Expectancy, Facilitating Conditions, Hedonic Motivation, and Perceived Risk do not have a significant influence. These findings confirm that Generation Z tends to adopt eSIM if the technology is capable of providing practical efficiency, enhancing social image, and promoting environmental sustainability values.